Meneropong Quality Education di Indonesia Pasca Pandemi - Prabowo, Gilang Agung (FKIP Universitas Wisnuwardhana, 2021)
Online learning during the COVID-19 pandemic, there are many obstacles experienced by schools and teachers so that Indonesia needs to find a new formula in designing quality education in accordance with the Sustainable Development Goals (SDGs). the type of this research is a literature study research. The data collection method used is by using Big Data Analysis. The results show that education in Indonesia is ranked 5th and 2nd place below Malaysia. In addition, more than 70% of classrooms at every level of education were damaged. The percentage of teachers who have the proper qualifications to teach at the elementary, junior high, and vocational levels in 2020 is 90%. However, this development is not matched by the percentage of teachers who are qualified to teach at the high school level which has decreased from the previous 97.95 percent to 89.93. Papua province occupies the lowest school participation rate in Indonesia and the Special Region of Yogyakarta has the highest school participation rate in Indonesia, namely 97.07%. Quoted from Katadata.co.id in 2020 that 92% of respondents aged 17 years and over learn to feel a lot of problems in participating in online learning.